Role of Parental Invasive Behaviour and Psychological Control on Health-Related Psychological Tendencies of Adolescents - Sharma, Saumya; Singh, Seema (International Journal of Psychosocial Rehabilitation, 2020)
Aim of the current research was to study the relationship between parental invasive behaviour, psychological control and health-related psychological tendencies. Three hundred adolescents (M= 17, SD= 0.85) of Delhi and NCR, India were selected as sample for the study. Image factoring and confirmatory factor analysis were used to test the hypothesis of the relationship between the variables. Results indicated that there was a significant association of psychological control with parental invasive behaviour and, psychological control with health orientation, however, parental invasive behaviour had partially significant association with adolescent’ health orientation. It was also found that psychological control was significantly associated with nine health-related psychological tendencies and, parental invasive behaviour was significantly associated with six health-related psychological tendencies. The study further revealed that psychological control and parental invasive behaviour as the predictors had a significant impact on eight and two health-related psychological tendencies among adolescent respectively.